Quality Control Framework for Statutory Audit of Financial Statements: A Comparative Study of USA, UK and India. Issue 2 (December 2016) - Saha, Siddhartha Sankar; Roy, Mitrendu Narayan
Abstract: Quality control of audit procedure has become extremely important in today's corporate environment in the backdrop of accounting irregularities and audit failures leading to corporate demise. Accounting firms control the quality of audit procedure with the help of the quality control standard (QCS) and specific auditing standard. These standards provide reasonable assurance of compliance with applicable regulation and issuance of the appropriate report by the engagement team. After discussing the international scenario of quality control framework, in this study a comparative analysis of quality control policies and procedures at firm and engagement in three select countries has been presented. The countries selected are the United States of America (USA), the United Kingdom (UK) and India. The study finds that the QCS and the auditing standard in all three countries are designed in line with International Standards on Auditing (ISAs) and International Standards on Quality Control (ISQC)-1. Naturally, quality control policies and procedures in three countries are comparable barring few minor differences. Based on these differences, it can be concluded that the quality control framework in the UK and India is more stringent as compared to the USA.